2005
DOI: 10.1093/ei/cbi055
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Leaks and the Fate of Small Community Air Service

Abstract: Using airline‐booking data from Sabre, this article documents the proportion of passengers who drive and fly from a hub airport, rather than take a commuter flight. If fewer passengers leaked to a hub, community airports would have more enplanements. Price and quality factors affecting leaks are econometrically estimated for the state of Wyoming. Fare differences, distance between the local airport and hub and the proportion of regional jets making the hub connection are important determinants. Short‐run elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…These findings are in line with the arguments in the literature reviewed (Innes and Doucet, 1990;Suzuki et al, 2003;Phillips et al, 2005;Zhang and Xie, 2005;Fuellhart, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are in line with the arguments in the literature reviewed (Innes and Doucet, 1990;Suzuki et al, 2003;Phillips et al, 2005;Zhang and Xie, 2005;Fuellhart, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Phillips et al (2005) found that level of regional jet services was an important determinant of traffic leakage in single-airport regions for both advance (leisure) and non-advance (business) purchase passengers. Local airports with 10 or more frequencies were more likely to have a regional jet service than a turboprop service.…”
Section: Literature Review Of Airport Competitionmentioning
confidence: 89%
See 2 more Smart Citations
“…In an intra-national "hub and spoke" flight network in which direct flights to the capital are unavailable, demand for transport to the local airport can leak to car transport for the trip to the central airport [17]. Using logistic regression with travel time to airport as an explanatory variable, [8] found that traffic leakages to large airports are commonly found at regional airports in Norway, particularly for leisure trips to the capital or abroad.…”
Section: Leakage Of Passengers To Larger Airportsmentioning
confidence: 99%